ANALYSIS OF LACTIC ACID BACTERIA WEISSELLA PARAMESENTEROIDES LM-21 AS PROBIOTIC CANDIDATE - Luthfia Muharram; Aflah Afina Nurdin; Rahma Risnaya; Sharen Ayuningtyas; Syifa Luthfia; Nurhaifa Azzahra (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2026)
Probiotics are live microorganisms that provide many health benefits. Weissella genus have been much research over this decade because probiotic potential. Weissella Paramesenteroides LM-21 isolated from Kimchi kiciwis leaf have health potential as glutathione antioxidant production. This research aims to analyze the ability of W. paramesenteroides LM-21 as a probiotic candidate.  The methodes are cell viability test at low pH (pH setting of 2.0; 3.0; 4.0; 7.0), antibacterial activity against E.coli and S.aureus, analysis production of exopolysaccharides (EPS) and qualitative analysis of short chain fatty acid (SCFA) by HPLC. The results are W.paramesentreroides LM-21 could survive at low pH (viability at pH 2 is 6.2 log CFU/mL); showed inhibition zone against E. coli was 0.8 mm and S. aureus was 0.5 mm; ability producing EPS with ropy phenotype and crude extract of 30 mg/mL; and SCFA (acetic acid based on a retention time of 10.688 minutes and propionic acid of 26.787 minutes). Based on the results of this research, can be concluded that W. paramesenteroides LM-21 has excellent potential as a probiotic candidate